Higher algebras and mesonic spectrum in two-dimensional QCD - Abdalla, E.; Abdalla, M. C B [UNESP] (Elsevier B.V., 1994)
We construct composite operators in two-dimensional bosonized QCD, which obey a W∞ algebra, and discuss their relation to analogous objects recently obtained in the fermionic language. A complex algebraic structure is unravelled, supporting the idea that the model is integrable. For singlets we find a mass spectrum obeying the Regge behavior.